A New Insight of the Photothermal Effect on the Highly Efficient Visible‐Light‐Driven Photocatalytic Performance of Novel‐Designed TiO2 Rambutan‐Like Microspheres Decorated by Au Nanorods. (21st January 2016) - Wang, Xiaotian; Zhu, Mingyun; Sun, Yibai; Fu, Wanlin; Gu, Qing; Zhang, Cheng; Zhang, Yuanjian; Dai, Yunqian; Sun, Yueming
Abstract : Photocatalyst‐assisted degradation of organic pollutants, which exhibits a novel strategy for solar‐energy utilization, possesses enormous potential in various applications. Extending the light‐absorption range in the spectrum of sunlight and improving light‐conversion efficiency are always primary issues to enhance the catalytic performance of these photocatalysts. Herein, a new structure of gold‐nanorod‐decorated TiO2 rambutan‐like microspheres is designed, which exhibits superior photocatalytic ability toward Rhodamine B in the range of visible light due to the 3D distribution of the TiO2 branches on the surface of the microspheres, which prompts the multireflection of photons. The absorption rate of photons is thereby tremendously enhanced. This is beneficial for the generation of hot electrons originating from the localized surface plasmonic resonance of Au nanorods, which can be used to both initiate the reaction and produce the photothermal effect. Hot electrons generated by a single Au nanorod in microspheres to initiate the degradation reaction can be as high as 2.5 times of those in the nanowires' counterpart. Moreover, the heating power of a single Au nanorod in microspheres reaches up to 4.4 times higher than that in nanowires, which further accelerates the degradation rate. The reaction pathway of visible‐light‐assisted RhB degradation catalyzed by Au/TiO2 microspheres goes through an initial N ‐deethylation process instead of the complete cycloreversion catalyzed by pure TiO2 microspheres under UV irradiation. This strategy of structure design for improved photon absorption, which achieves high degradation rate and photothermal effect, is promising for the development of novel photocatalysts. Abstract : The novel design of a rambutan‐like TiO2 microsphere structure greatly improves the photothermal and photocatalytic performance due to the multireflection of photons on the surface of intensively distributed TiO2 branches.